ANALISIS FUNGSI RUANG TERBUKA HIJAU DI KOTA BAGANSIAPIAPI - Eka Wahyuni; Nofrizal Nofrizal; Mardianto Manan (Program Pascasarjana Universitas Riau, 2017)
Green Open Space of Bagansiapiapi has different functions, the difference in community activity, the function of Green Open Space in Bagansiapiapi is ecologically, socially, culturally, economically and aesthetically uneven. The purpose of this study is to describe how the function of RTH ecologically, socio-culturally, economically, and aesthetically on the object of GOC in Bagansiapiapi. This research was conducted at Green Open Spaces (GOC) in Bagansiapiapi by using survey method by using questionnaire. Based on the result of the calculation MPE method, it is obtained the priority result. GOC used as research object in Bagansiapiapi according to the expert is City Park, City Forest, Coastal Nature Park of Rokan River Batu 6, Cultural Park, and Jalan Bintang Sungai Pabrik Park. Ecologically, the each function of GOC in Bagansiapiapi was carried out in five parks, namely City Park, City Forest, Coastal Nature Park of Rokan River Batu 6 which have good category, while Cultural Park and Jalan Bintang Sungai Pabrik Park have not good category. A micro climate regulator becomes the indicator with the highest index value due to the presence of plants that can block the sunlight and lower the environmental temperature on RTH. Socio culturally, the function of GOC in the Coastal Nature Park of Rokan River Batu 6 and Cultural Park is best category, while the City Forest is bad category. The criteria as a place of recreation becomes the indicator with the highest index value because the GOC is indeed used by the community as a place of family gathering, playing, discussing, and culinary because the location is beautiful, cool and calm. Aesthetically, the function of GOC for City Park and Cultural Park is best category, while the Coastal Nature Park of Rokan River Batu 6 and Jalan Bintang Sungai Pabrik Park get good category. City Forest have bad category in aesthetically function. Beautify the urban environment and stimulate the urban creativity is the higest index indicator due to the combination of soft and hard scape elements as well as its existence as a center of urban activity.